PREDICTION OF BABY BIRTH RATE USING NAÏVE BAYES CLASSIFICATION ALGORITHM IN RANDAU VILLAGE - Magda Kitty Hartono; Hendry Hendry (Informatika, Universitas Jenderal Soedirman, 2022)
The birth rate is one of the factors increasing the rate of population growth. Birth or fertility can affect the population, getting more lower of birth rate in an area, the higher the life expectancy in that area. The number of births in Randau Jekak Village is increasing every year. The Naïve Bayes algorithm can be used to predict the future births rate because this algorithm is a simple algorithm and uses a lot of data as information in collecting data groups, and with data mining techniques it can see the predictive pattern of each variable and test. The testing data and the training data are expected to help the Village Institution or Office in Randau Jekak to suppressing the rate of population growth which increases every year. The results of this study can be concluded that the Naïve Bayes Algorithm is suitable for predicting the birth rate of babies in Randau Jekak Village with the classification technique, the birth rate in Randau Jekak Village in 2021 is High. The results of this data will be very useful for the Randau Jekak Village office in suppressing the rate of population growth in the coming year.